Genetic stratification of inherited and sporadic phaeochromocytoma and paraganglioma: implications for precision medicine. (20th October 2020) - Casey, Ruth; Neumann, Hartmut P H; Maher, Eamonn R
Abstract: Over the past two decades advances in genomic technologies have transformed knowledge of the genetic basis of phaeochromocytoma and paraganglioma (PPGL). Though traditional teaching suggested that inherited cases accounted for only 10% of all phaeochromocytoma diagnosis, current estimates are at least three times this proportion. Inherited PPGL is a highly genetically heterogeneous disorder but the most frequently results from inactivating variants in genes encoding subunits of succinate dehydrogenase. Expanding knowledge of the genetics of PPGL has been translated into clinical practice by the provision of widespread testing for inherited PPGL. In this review, we explore how the molecular stratification of PPGL is being utilized to enable more personalized strategies for investigation, surveillance and management of affected individuals and their families. Translating recent genetic research advances into clinical service can not only bring benefits through more accurate diagnosis and risk prediction but also challenges when there is a suboptimal evidence base for the clinical consequences or significance of rare genotypes. In such cases, clinical, biochemical, pathological and functional imaging assessments can all contribute to more accurate interpretation and clinical management.